The essence of phinisi ship building for “Punggawa” in bira village of Bulukumba regency - Suparman Suparman; Shermina Oruh; Syamsu A Kamaruddin; Andi Agustang (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to analyze how the essence of making phinisi ships for retainers. Data was collected by observation, interviews and documentation. While the data analysis used the interactive method of Miles and Huberman with three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the core of the process of making a phinisi ship for the retainer is a ship made with a retainer who has a strong inner bond, the retainer feels that making a phinisi ship is a matter of pride because being a retainer is a matter of pride. a long process and a very large mandate. Making phinisi boats for courtiers is a livelihood to support their families. In addition, the researcher also revealed that family relations and mutual respect are still very strong which are useful for providing maximum results, phinisi shipbuilding must apply teamwork, thoroughness, hard work and uphold the existing local culture. The relationship between followers and workers respects each other and upholds deliberation when obstacles arise.